1986
DOI: 10.1677/joe.0.1090291
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone metabolites do not participate in the control of hypothalamic LH-releasing hormone

Abstract: To determine whether the ability of testosterone to increase intrahypothalamic LH-releasing hormone (LHRH) in orchidectomized rats might be explained by the conversion of the hormone into either its 5 alpha-reduced or oestrogenic metabolites, testosterone, 5 alpha-androstan-17 beta-ol-3-one (DHT), 5 alpha-androstane-3 alpha,17 beta-diol (3 alpha-diol) and 5 alpha-androstane-3 beta,17 beta-diol (3 beta-diol) (2 mg/rat per day for 6 days) and oestradiol (0.1, 0.5, 1.0 and 5.0 micrograms/rat per day for 6 days) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
(56 reference statements)
2
9
0
Order By: Relevance
“…The present data confirm, first of all, previous evidence of this (Zanisi et al 1986) and other laboratories (Shin & Howitt 1975, 1976Kalra et al 1977;Kalra & Kalra 1980;Bourguignon et al 1984) indicating that, in male rats, long-term (5 weeks) orchidectomy results in a decrease of intrahypothalamic GnRH stores. As mentioned in the Introduction, this decrease is due to an increased release of GnRH into the pituitary portal vessels (Eskay et al 1977;Sarkar & Fink 1980;Clayton & Catt 1981;Conne 1982;Limontaetal.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present data confirm, first of all, previous evidence of this (Zanisi et al 1986) and other laboratories (Shin & Howitt 1975, 1976Kalra et al 1977;Kalra & Kalra 1980;Bourguignon et al 1984) indicating that, in male rats, long-term (5 weeks) orchidectomy results in a decrease of intrahypothalamic GnRH stores. As mentioned in the Introduction, this decrease is due to an increased release of GnRH into the pituitary portal vessels (Eskay et al 1977;Sarkar & Fink 1980;Clayton & Catt 1981;Conne 1982;Limontaetal.…”
Section: Discussionsupporting
confidence: 92%
“…It is known that, in male rats, orchidectomy in¬ duces a significant decrease of the GnRH content of the mediobasal hypothalamus (MBH) (Shin & Howitt 1975, 1976Kalra et al 1977; Kalra & Kalra 1980;Bourguignon et al 1984;Zanisi et al 1986). This decrease is due to an increased release of GnRH into the pituitary portal vessels as shown by direct measurements (Eskay et al 1977;Sarkar & Fink 1980) …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, this problem is still poorly understood. Some authors reported that 5o~-reduction of testosterone is not necessary for the regulation of gonadotropin secretion in rats [43,68].…”
Section: N N Blokhin Russian Ontological Research Center Russian Amentioning
confidence: 99%
“…Obviously, it is important whether or not androgen metabolites act at the level of rat pituitary gland or hypothalamus, or they affect both these structures. Some authors assume that androgens exert their effects at the level of the pituitary gland [35,68], while others believe that these hormones affect the hypothalamus [28,29]. It was also reported that androgens regulate gonadotropic functions by acting simultaneously on the pituitary gland and hypothalamus [27,34].…”
Section: N N Blokhin Russian Ontological Research Center Russian Amentioning
confidence: 99%